Sustainable tourism strategies in the town of Palomino, department of La Guajira - Barraza Bermudez, Clara Vanessa; Rodríguez Diaz, Francisco José; Barraza Bermudez, Clara Vanessa; Rodríguez Diaz, Francisco José (Corporación Universitaria Americana, 2023)
i) Introduction: Tourism is one of the most relevant economic activities worldwide and a potential engine for the development of developing communities; ii) objective: This article aims to propose sustainable tourism strategies in the town of Palomino, department of La Guajira within the framework of economic reactivation after the covid 19 pandemic. iii)methodology: The research is based on a study with a mixed approach and descriptive scope, where questionnaire surveys were applied to 47 hostels/hotels located in Palomino and registered with the Chamber of Commerce of La Guajira. The data were statistically analyzed in SPSS. iv) results: Among the most relevant findings, it is considered that the problem of coastal erosion, the lack of tourist infrastructure and the poorcoverage of public services are a barrier to sustainability in the territory; v) conclusions: Finally, actions are recommended to strengthen the economy, preserve identity and conserve natural and environmental resources, promote the destination, implement digital marketing strategies and enhance big data that accelerate economic recovery after the crisis generated by the COVID-19 pandemic.